EFL learning strategies used by female undergraduate students / Wafa Ismail Saud - Wafa, Ismail Saud (2009)
The aim of the present study was to provide an accurate and holistic description of the language learning strategies used by female EFL undergraduate students, as well as to explore the relationship of language learning strategies with the two variables: major field of study and performance level in the English language. It also aimed at specifying the English language learning strategies that were associated with the four language skills. The survey method was used on a sample of 264 female EFL undergraduate students who were enrolled in the first and second year of their undergraduate degree programme. Their majors were Medicine, English Language, Computer Science and Biology. Four tools were employed for eliciting information: Oxford’s (1990) Strategy Inventory for Language Learning (SILL), interviews, class observations and an achievement test. The findings indicated that while EFL students employed a variety of language learning strategies, the cognitive and meta-cognitive ones were more frequently used than others. In general, EFL students reported medium overall strategy use. More importantly, the results provided new evidence for the relationship between strategy use and the two variables: major field of study and English language performance level. Medical, English and Computer Science majors used the meta-cognitive strategy category most often followed by the cognitive one. On the other hand Biology majors used the compensation strategy category most frequently followed by the meta-cognitive one. Similarly, results indicated that Medical students used the memory strategy category more than the students in all the other major fields of study. In general, Medical students reported the highest use of overall strategy while the Computer Science and iv Biology students reported the least use of overall strategy. Regarding the relationship between strategy use and year level of the students, results revealed that both first and second year students share most of the strategies and that they are meta-cognitive strategy users. In general, they both reported medium overall strategy use. Additional results confirm the conclusion that language learning strategies are related to language proficiency. The findings indicated that proficient learners do not necessarily use more strategies but rather use different and more appropriate ones. Finally, the findings specified the language learning strategies that were associated with each of the four language skills. The study concluded by bringing together the key findings, recommendations for EFL teachers and suggested areas for further research.